2011
DOI: 10.1038/jp.2011.153
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of fetal ductal constriction after maternal restriction of polyphenol-rich foods: an open clinical trial

Abstract: Objective: To test the hypothesis that maternal restriction of polyphenolrich foods (PRF), which, like non-steroidal anti-inflammatory drugs (NSAID), inhibit prostaglandin synthesis in the third trimester, reverse fetal ductal constriction (DC). Study Design:An open clinical trial of 51 third trimester fetuses with DC with no history of NSAID intake was designed. All mothers were submitted to a food frequency questionnaire and were oriented to withdrawl PRF, being reassessed after 3 weeks. Doppler parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
1
35
0
1
Order By: Relevance
“…In previous studies from our group, Zielinsky and coworkers demonstrated that the intake of PRF during late pregnancy was able to induce premature DA constriction in human fetuses and recently reported the reversal of ductal constriction after pregnant women were instructed not to consume foods with high polyphenol contents . These findings were corroborated by Kapadia and coworkers, who associated the prenatal DA closure with maternal ingestion of a juice blend containing anthocyanins and proanthocyanidins …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In previous studies from our group, Zielinsky and coworkers demonstrated that the intake of PRF during late pregnancy was able to induce premature DA constriction in human fetuses and recently reported the reversal of ductal constriction after pregnant women were instructed not to consume foods with high polyphenol contents . These findings were corroborated by Kapadia and coworkers, who associated the prenatal DA closure with maternal ingestion of a juice blend containing anthocyanins and proanthocyanidins …”
Section: Discussionmentioning
confidence: 57%
“…The studies available on the DA dynamics are basically based on the effect of anti‐inflammatory drugs (NSAIDs or glucocorticoids) either in inducing premature DA constriction or in patent ductus arteriosus cases, in which the pharmacological closure of the DA is searched . Therefore, few studies have been conducted with a premature DA constriction without any relation to NSAIDs intake, which are anti‐inflammatory agents, whereas polyphenols in general present simultaneous anti‐inflammatory and antioxidant effects, as shown in our results.…”
Section: Discussionmentioning
confidence: 73%
“…As mentioned above, this hypothesis was based on knowledge obtained in the past years, and particularly with the demonstration of reversal of the ductal constrictive effects following maternal restriction of polyphenol-rich foods 1 . Ductal constriction is a non-categorical, "yes or no" phenomenon, but rather a continuous spectrum with increasing severity related to the clinical manifestations of right ventricular overload, tricuspid and/or pulmonary regurgitation and Doppler-echocardiographic findings of increased systolic and mainly diastolic ductal flow velocities, as well as decrease of the ductal pulsatility index.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that ductal constriction occurring in the absence of maternal intake of anti-inflammatory drugs in the third trimester of pregnancy is reversed by dietary restriction of polyphenol-rich foods, such as herbal teas, mate, coffee, dark chocolate, coffee, from grape, orange, tangerine, red fruits, apple and olive oil 1 . Other clinical and experimental evidences support the association of changes in fetal ductus arteriosus flow and maternal consumption of foods with high concentration of natural anti-inflammatory substances such as polyphenols 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios clínicos y experimentales han demostrado que el consumo materno de sustancias ricas en polifenoles, tales como infusiones, zumo de naranja, uva, chocolate y manzana, afectan la hemodinámica normal del conducto arterioso, y por tanto se ha planteado la necesidad de cambiar la orientación de la dieta materna con el objetivo de limitar la ingestión de este tipo de alimentos en el tercer trimestre 9 .…”
Section: Discussionunclassified